OPTIMALISASI PERAN BIMBINGAN KONSELING DI SEKOLAH - admin, admin; Handayani, Suci (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2017)
Legislation No. 14 of 2005 on Teachers and Lecturers article 35 paragraph 1 of the workload of teachers include diapers that plan learning activities, implementing learning, assessing learning outcomes, participant guide and train students and carry out additional duties. Teacher is a major factor in the overall educational process. As an educator, the teacher holds a lot of different roles to perform. The role is a particular pattern of behavior which are characteristics all officers of a particular job or position. The role of the teacher is any pattern of behavior that are characteristic of professorship teachers to do the job. This role includes various types of patterns of behavior, both in activities within the school and outside of school. Teachers who are considered good are those who succeed in these roles. It plays as well as possible, meaning that it can show a pattern of behavior in accordance with his position and accepted by the environment and society. Optimizing the role of guidance and counseling to all residents, especially school teacher empowerment is one alternative in providing services to students. So it is in need or presented a teacher who can handle it all, where teachers have met the criteria, and the expertise that address the problem students, to provide guidance and counseling services.